Low-reflectivity lens coating and method of making the same

CN122979827APending Publication Date: 2026-10-27HUIZHOU JIUJIU OPTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611120338.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种低反射率镜片镀膜及其制备方法,用于解决现有技术中制备镜片所用的真空镀膜工艺难以同时兼顾可见光与近红外区域的低反射要求,且使用寿命需要进一步提高的技术问题

Benefits of technology

1.本发明中采用低折射率材料SiO2与高折射率材料Ti3O5的交替组合,在400~1000nm宽波段范围内形成多光束干涉相消效应,第一层SiO2(15~30nm)作为基体与膜系之间的过渡层,其厚度匹配Ti3O5层的光学相位,减少基体界面的反射;第二层Ti3O5(10~25nm)与第三层SiO2(30~55nm)、第四层Ti3O5(40~70nm)与第五层SiO2(20~40nm)构成两组主干涉腔体,负责宽波段平均反射率的整体压制;第六层Ti3O5(8~18nm)与第七层MgF2(85~130nm)构成表层相位匹配层,专门针对近红外波段实现反射率的深度抑制。各膜层分别承担不同波段的相位补偿作用,各层光学厚度共同决定整个膜系的干涉谱线,使得最终镀膜在400~1000nm波段的平均反射率≤0.09%,同时在850nm±50nm范围内反射率≤0.1%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a kind of low reflectivity lens coating and preparation method thereof, belong to glass coating technical field;The application is used to solve the technical problems that the vacuum coating process used in the prior art for preparing lens is difficult to simultaneously consider the low reflection requirements of visible light and near-infrared region, and service life needs to be further improved;Among them, the low reflectivity lens coating includes 7 layers of film structure from the surface of the lens substrate outward in turn, wherein the first layer is SiO2, the thickness is 15-30nm;The second layer is Ti3O5, the thickness is 10-25nm;The third layer is SiO2, the thickness is 30-55nm;The fourth layer is Ti3O5, the thickness is 40-70nm;The fifth layer is SiO2, the thickness is 20-40nm;The sixth layer is Ti3O5, the thickness is 8-18nm;The seventh layer is MgF2, the thickness is 85-130nm;Among them, the average reflectivity of the low reflectivity lens coating in the 400-1000nm wave band is less than or equal to 0.09%, and the reflectivity in the range of 850nm±50nm is less than or equal to 0.1%;The low reflectivity lens coating prepared by the application can be used for preparing low reflectivity lens, low reflectivity glass and security lens for vehicle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass coating technology, specifically to a low-reflectivity lens coating and its preparation method. Background Technology

[0002] Glass, as the most commonly used substrate for lenses, is the preferred substrate for various myopia lenses, sunglasses lenses, and optical instrument lenses due to its stable physicochemical properties, excellent light transmittance, and processability. However, the average reflectivity of ordinary glass surfaces without coating modification treatment can reach about 8% for visible light. This not only reduces the overall light transmittance of the lens, leading to a decrease in image clarity, but also produces reflected glare, interfering with the user's vision and significantly reducing the user experience. Therefore, it is necessary to prepare low-reflection coatings on the glass surface to improve its optical performance. The industry generally adopts the method of coating anti-reflection films on the lens substrate surface to reduce the surface reflectivity of the lens. Currently, most mainstream optical anti-reflection film systems on the market are specifically optimized for the 400-700nm visible light band to meet the needs of human vision and conventional visible light imaging equipment. However, with the iterative upgrade of intelligent optical equipment, security monitoring, intelligent terminals, and other devices generally integrate infrared sensing and supplementary lighting imaging modules. The industry mainstream uses 850nm and 940nm near-infrared LEDs as supplementary lighting sources to achieve day and night all-weather imaging, human body sensing, distance measurement and recognition functions. Traditional single visible light antireflective coatings suffer from significant wavelength compatibility limitations. Their optical performance is excellent only in the visible light range, failing to maintain stable antireflection effects in the 700-1000nm near-infrared operating band, where reflectivity spikes dramatically to 1%~3%. This high infrared reflectivity causes severe light loss from the lens surface, reducing not only the utilization rate of infrared light incident light but also leading to imaging problems such as lens glare, stray light, and fogging. This directly results in blurry, washed-out images and loss of detail in nighttime imaging of vehicle security lenses, significantly reducing the accuracy of nighttime monitoring and identification.

[0003] Chinese patent CN118688882A discloses a low-reflectivity lens and its preparation method. The low-reflectivity lens includes a substrate and a first coating layer, a second coating layer and a third coating layer sequentially disposed on the substrate. The low-reflectivity lens prepared by this patent has a reflectivity of less than 0.1% in the 400-750nm wavelength band, but its applicable range does not include the 850nm and 940nm near-infrared regions. Chinese patent CN103698901B discloses a 1.56 refractive index low reflectivity film resin lens and its coating method. The 1.56 refractive index low reflectivity film resin lens includes a resin lens, a vacuum film, and a hardening film. The vacuum film system is a nine-layer anti-reflection and anti-reflection film, comprising: a first low refractive index film, a second high refractive index film, a third low refractive index film, a fourth high refractive index film, a fifth low refractive index film, a sixth high refractive index film, a seventh low refractive index film, an eighth low refractive index film, and a ninth fluoride layer. The vacuum coating process disclosed in this invention involves a silicone hardening film with a large difference in thermal expansion coefficients and multiple layers in the vacuum film system. After thermal cycling, the film layers crack and peel off in sheets, and its service life needs further improvement. Summary of the Invention

[0004] The purpose of this invention is to provide a low-reflectivity lens coating and its preparation method, which solves the technical problem that the vacuum coating process used in the prior art for preparing lenses is difficult to simultaneously meet the low reflectivity requirements in the visible light and near-infrared regions, and the service life needs to be further improved.

[0005] To achieve the above objectives, the present invention provides a low-reflectivity lens coating comprising a seven-layer film structure from the surface of the lens substrate outwards. The first layer is SiO2 with a thickness of 15-30 nm; the second layer is Ti3O5 with a thickness of 10-25 nm; the third layer is SiO2 with a thickness of 30-55 nm; the fourth layer is Ti3O5 with a thickness of 40-70 nm; the fifth layer is SiO2 with a thickness of 20-40 nm; the sixth layer is Ti3O5 with a thickness of 8-18 nm; and the seventh layer is MgF2 with a thickness of 85-130 nm. Among them, the low-reflectivity lens coating has an average reflectivity of ≤0.09% in the 400~1000nm wavelength band and ≤0.1% in the 850nm±50nm range.

[0006] A method for preparing a low-reflectivity lens coating, the method comprising: S1: The lens substrate is loaded into the coating machine fixture, vacuumed, heated, in-situ low-energy plasma surface activation, and ion beam cleaning to obtain the pretreated lens. S2: Layers 1 to 7 are deposited sequentially on the pretreated lens substrate surface in an order from the lens substrate surface outward to form an antireflective coating system; S3: Deposit all film layers, post-process, to obtain a low-reflectivity lens coating; The antireflective coating system consists of the following layers from the surface of the lens substrate outwards: a first layer of SiO2; a second layer of Ti3O5; a third layer of SiO2; a fourth layer of Ti3O5; a fifth layer of SiO2; a sixth layer of Ti3O5; and a seventh layer of MgF2. In S1, the lens substrate is glass; In S1, the vacuum level after evacuation is ≤2.0×10⁻⁶. -3 Pa; The third and fifth SiO2 layers both follow the same preparation steps as the first SiO2 layer, and deposition only begins after the Ti3O5 layer is prepared and the interlayer treatment is completed. The fourth and sixth Ti3O5 layers both follow the same preparation steps as the second Ti3O5 layer, and deposition only begins after the SiO2 layer is prepared and the interlayer treatment is completed.

[0007] Preferably, the preparation of the first SiO2 layer includes the following steps: The pretreated lens temperature was maintained at 110~130℃. An oxygen-argon mixture with a flow rate ratio of 2:1 was introduced into the ion source, with oxygen at 12 sccm and argon at 6 sccm. The ion source power was 340~360W. SiO2 was evaporated using an electron beam at a deposition rate of 0.2~0.4 nm / s. The radio frequency bias was 70W and kept on throughout the process until the deposition of this layer was completed.

[0008] Preferably, the preparation of the second Ti3O5 layer includes the following steps: After the SiO2 layer preceding the Ti3O5 layer is deposited and the interlayer treatment is completed, the temperature is lowered to 100-120℃, and a mixture of oxygen and argon with a flow rate ratio of 3:1 is introduced, with 15 sccm of oxygen and 5 sccm of argon. The ion source power is 400W. Ti3O5 is evaporated using an electron beam at a deposition rate of 0.03-0.05 nm / s, with a 100W RF bias maintained throughout. When 1-2.2nm of deposition is achieved, the RF bias is reduced to 70W, the evaporation rate is increased to 0.1-0.25 nm / s, the ion source power is maintained at 180W, and the working gas is switched to a mixture of oxygen and argon in equal volume ratios at a total flow rate of 20 sccm, and deposition continues. When only 5nm of the target thickness of the Ti3O5 layer remains, the ion source gas is switched back to oxygen at a flow rate of 15 sccm until the Ti3O5 layer deposition is complete.

[0009] Preferably, after the deposition of any one layer in the antireflection film system is completed and before the deposition of the next layer begins, an interlayer treatment is further included, specifically: If the newly completed film is a Ti3O5 layer, maintain the lens temperature at 100~120℃, turn on the ion source, set the power to 100w, and introduce argon gas at a flow rate of 10~15 sccm to bombard the newly completed film for 2 minutes. If the newly completed film is a SiO2 layer, maintain the lens temperature at 110~130℃, turn on the ion source, set the power to 150~200w, introduce oxygen at a flow rate of 10~15 sccm, and simultaneously apply a 70w radio frequency bias voltage for 30~40s.

[0010] Preferably, the preparation of the 7th MgF2 layer includes the following steps: Step (1) First deposition: The ion source power was set to 230W, the argon gas flow rate was 10~12 sccm, the MgF2 evaporation rate was 0.3~0.4 nm / s, the radio frequency bias was turned off, and the first deposition thickness was 4~6nm. Step (2) Second deposition: During the second deposition, the ion source power was slowly reduced from 230W to 100W, the evaporation rate was 0.4–0.6 nm / s, and the thickness of the second deposition was 20–24 nm. Step (3) Third deposition: The ion source power was set to 100W, the evaporation rate was 0.4–0.6 nm / s, and the thickness of the third deposition was 61–100 nm. After step (4) deposition is completed, turn off the MgF2 electron beam baffle, maintain the ion source power at 100W and the argon flow rate at 10~12sccm, bombard for 10~15min, and then turn off the ion source; In steps (1), (2), (3), and (4), the lens temperature is maintained at 100~120℃, and the radio frequency bias voltage is kept off.

[0011] Preferably, the post-processing steps are as follows: After all the film layers are deposited, maintain vacuum for 15 minutes, purge with dry nitrogen to atmospheric pressure, and then slowly cool to 50°C at a rate of 2°C / min before removing.

[0012] Preferably, the in-situ low-energy plasma surface activation conditions are: using a radio frequency power supply, oxygen flow rate of 10~15 sccm, power of 150~200w, and time of 60~180s.

[0013] Preferably, the ion beam cleaning is performed using a radio frequency ion source with an Ar flow rate of 10-20 sccm, a power of 300-500w, and a cleaning time of 3-5min.

[0014] A low-reflectivity lens, comprising the aforementioned low-reflectivity lens coating.

[0015] A low-reflectivity glass, comprising the aforementioned low-reflectivity lens coating.

[0016] A security lens for vehicles includes the aforementioned low-reflectivity lens coating.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In this invention, an alternating combination of low-refractive-index material SiO2 and high-refractive-index material Ti3O5 is used to form a multi-beam interference destructive effect in a wide wavelength range of 400~1000nm. The first layer of SiO2 (15~30nm) serves as a transition layer between the substrate and the film system, and its thickness matches the optical phase of the Ti3O5 layer, reducing reflection at the substrate interface. The second layer of Ti3O5 (10~25nm) and the third layer of SiO2 (30~55nm), the fourth layer of Ti3O5 (40~70nm) and the fifth layer of SiO2 (20~40nm) constitute two sets of main interference cavities, which are responsible for the overall suppression of the average reflectivity in the wide wavelength range. The sixth layer of Ti3O5 (8~18nm) and the seventh layer of MgF2 (85~130nm) constitute the surface phase matching layer, which is specifically designed to achieve deep suppression of reflectivity in the near-infrared band. Each film layer performs phase compensation in different wavelength bands, and the optical thickness of each layer together determines the interference spectrum of the entire film system, so that the average reflectivity of the final coating is ≤0.09% in the 400~1000nm wavelength band, and ≤0.1% in the 850nm±50nm range.

[0018] 2. In the method for preparing low-reflectivity lens coating provided by the present invention, a combination of plasma surface activation and ion beam cleaning is used for pretreatment. Plasma activation increases the surface energy of the substrate, providing highly active nucleation sites for subsequent film deposition, while ion beam cleaning ensures the bonding force between the substrate and the first layer of SiO2. The two work together to optimize the substrate pretreatment effect, which not only solves the problems of insufficient surface activity and limited bonding force improvement in single treatment methods, but also constructs a clean, uniform, and sufficiently active interface for the subsequent deposition of antireflective film, making the structure of each film layer more uniform and dense, effectively reducing film defects and interface stress, and improving the bonding stability between the film layer and the substrate as well as between the film layers. The first layer of SiO2, in conjunction with ion-assisted deposition (IAD) and radio frequency bias during PVD deposition, improves the mobility and reactivity of oxygen atoms, promotes film densification, and reduces oxygen vacancy defects caused by SiO2 decomposition during electron beam evaporation, thus ensuring the optical transmittance of the film in the short-wavelength region. The second layer of Ti3O5 is prepared by segmented deposition. Compared with single-segment deposition, stress release and grain rearrangement are completed between each segment, which reduces film defects and improves the stability of refractive index. The interlayer treatment method for each SiO2 layer helps to fill the oxygen vacancy defects generated by the decomposition of SiO2 during electron beam evaporation, while eliminating the internal stress of the film. Each Ti3O5 layer is subjected to argon ion physical bombardment at 100~120℃. Through the momentum transfer of high-energy particles, the film atoms are displaced and rearranged, eliminating the micropores between the columnar crystals of Ti3O5. At the same time, a moderate tensile stress is introduced to balance the compressive stress generated during the subsequent deposition of SiO2 layers. This method is perfectly matched with the deposition temperature, which avoids the thermal stress introduced by additional heating and cooling, and achieves targeted repair of the two types of film defects in SiO2 and Ti3O5 layers.For the outermost MgF2 layer, this invention proposes a step-by-step deposition combined with ion bombardment post-treatment. A 4-6 nm layer is deposited using a high ion source power and low deposition rate. High-energy ions are used to suppress the heterogeneous crystallization tendency of MgF2 on the glass substrate, increasing the initial nucleation density and forming an amorphous transition layer. The ion source power is gradually reduced from 230 W to 100 W, depositing 20-24 nm. This gradual power change avoids stress jumps caused by abrupt changes, resulting in a smooth transition of the film structure. A 61-100 nm main layer is deposited using a low power of 100 W. The low ion energy reduces the internal stress of the film. To eliminate defects, after deposition, the substrate temperature is maintained at 100~120℃, and the ion source is 100W with argon for 10~15 minutes. This long-term low-energy bombardment achieves secondary densification and pore sealing of the film. As a result, the crystallinity of the MgF2 film gradually changes layer by layer, and the stress is released steadily. Compared with the traditional single-stage deposition, this further reduces the internal stress of the film. The post-bombardment treatment completely seals the pinhole channels between columnar crystals, giving the outermost MgF2 layer excellent moisture resistance and corrosion resistance, ensuring the long-term stability of the coating in humid and hot environments, and extending its service life. In this invention, after all seven film layers are deposited, a vacuum holding period of 15 minutes is followed by purging with dry nitrogen to atmospheric pressure, and then slow cooling to 50°C at a rate of 2°C / min before removal. The vacuum holding stage allows for the complete desorption of residual gas and adsorbed water molecules within the film layers, preventing the formation of scattering centers. The slow cooling rate of 2°C / min ensures that the three materials with significantly different coefficients of thermal expansion (SiO2, Ti3O5, and MgF2) can fully relax during cooling, preventing thermal stress cracking due to temperature gradients. The post-processing addresses the macroscopic stress issues of the entire film system and substrate by achieving thermal stress relaxation through slow cooling, preventing cracking and peeling, and ensuring long-term reliability. Simultaneously, uniform and stable internal stress helps maintain the refractive index of each film layer, thus ensuring the stability of the multilayer interference effect and maintaining a stable average low reflectivity in the 400–1000 nm wavelength range. This avoids localized chromatic aberration or substandard reflectivity caused by refractive index shifts due to uneven stress.

[0020] 3. By optimizing the film structure design, this invention achieves a coating structure that simultaneously meets the low-reflection requirements in both the visible and near-infrared regions. The anti-reflection and anti-reflection effect covers a wider wavelength range, effectively reducing visual interference from excess light in various scenarios. The low-reflection lens coating prepared using this invention not only has a lower average reflectance and superior visible-near-infrared broadband anti-reflection and anti-reflection effect, but also features a stable film structure and good process compatibility. It is particularly suitable for applications requiring low reflection in the visible-near-infrared broadband, such as automotive lenses and security monitoring lenses. Furthermore, the preparation method of this invention is compatible with existing vacuum coating production systems, exhibiting good process stability and high yield, making it suitable for large-scale industrial production and possessing high application value. Attached Figure Description

[0021] Figure 1 This is a graph showing the relationship between reflectivity and wavelength for the low-reflectivity lens coatings of Embodiment 1 and Comparative Example 1 of the present invention. Figure 2 The angle-resolved reflectance spectrum of the low-reflectivity lens coating of Embodiment 1 of the present invention; Figure 3 The bar graphs show the water contact angle test results of the low reflectivity lens coating surfaces in Examples 1-5 and Comparative Example 1 of this invention. Detailed Implementation

[0022] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example

[0023] This embodiment provides a method for preparing a low-reflectivity lens coating, including the following steps: S1: The glass substrate is placed into the coating machine fixture, evacuated to a vacuum degree ≤2.0×10⁻³Pa, heated to 110℃, activated by in-situ low-energy plasma, and cleaned by ion beam to obtain the pretreated lens; The in-situ low-energy plasma surface activation conditions are as follows: using a radio frequency power supply, oxygen flow rate of 10 sccm, power of 150w, and time of 180s. Specifically, the ion beam cleaning process involves using a radio frequency ion source with an Ar flow rate of 10 sccm, a power of 300w, and a cleaning time of 5min. S2: On the pretreated lens substrate surface, in the order from the lens substrate surface outward, the following layers are deposited sequentially: the first layer of SiO2; the second layer of Ti3O5; the third layer of SiO2; the fourth layer of Ti3O5; the fifth layer of SiO2; the sixth layer of Ti3O5; and the seventh layer of MgF2 to form an antireflection film system. The third and fifth SiO2 layers both adopted the same preparation steps as the first SiO2 layer, and their deposition was only started after the Ti3O5 layer was prepared and the interlayer treatment was completed. The fourth and sixth Ti3O5 layers both adopted the same preparation steps as the second Ti3O5 layer, and the deposition process only began after the SiO2 layer was prepared and the interlayer treatment was completed. The preparation of the first SiO2 layer includes the following steps: The pretreated lens temperature was kept at 110℃. An oxygen and argon mixture with a flow rate ratio of 2:1 was introduced into the ion source, with oxygen at 12 sccm and argon at 6 sccm. The ion source power was 340W. SiO2 was evaporated by electron beam at a deposition rate of 0.2 nm / s. The radio frequency bias voltage was 70W and kept on throughout the process until the deposition of this layer was completed. The preparation of the second Ti3O5 layer includes the following steps: After the SiO2 layer preceding the Ti3O5 layer is deposited and the interlayer treatment is completed, the temperature is lowered to 100℃, and a mixture of oxygen and argon with a flow rate ratio of 3:1 is introduced, with 15 sccm of oxygen and 5 sccm of argon. The ion source power is 400W. Ti3O5 is evaporated using an electron beam at a deposition rate of 0.03 nm / s. The RF bias is maintained at 100W throughout the process. When 1 nm of deposition is reached, the RF bias is reduced to 70W, the evaporation rate is increased to 0.1 nm / s, the ion source power is maintained at 180W, and the working gas is switched to a mixture of oxygen and argon in equal volume ratios at a total flow rate of 20 sccm. Deposition continues. When only 5 nm of the target thickness of the Ti3O5 layer remains, the ion source gas is switched back to oxygen at a flow rate of 15 sccm until the Ti3O5 layer deposition is complete. This includes interlayer treatment after the deposition of any one layer in the antireflection membrane system and before the deposition of the next layer, specifically: The newly completed film is a Ti3O5 layer. The lens temperature is maintained at 100℃, the ion source is turned on, the power is set to 100w, and argon gas with a flow rate of 10 sccm is introduced to bombard the newly completed film for 4 minutes. If the newly completed film is a SiO2 layer, maintain the lens temperature at 110℃, turn on the ion source, set the power to 150W, introduce oxygen at a flow rate of 10 sccm, and simultaneously apply a 70W radio frequency bias voltage for 40s. The preparation of the 7th MgF2 layer includes the following steps: Step (1) First deposition: control the lens temperature to 100℃, set the ion source power to 230w, introduce argon gas with a flow rate of 10 sccm, MgF2 evaporation rate to 0.3 nm / s, turn off the radio frequency bias, and the first deposition thickness is 4nm; Step (2) Second deposition: The lens temperature is controlled at 100℃. During the second deposition, the ion source power is set to slowly decrease from 230w to 100w. During this period, the evaporation rate is 0.4 nm / s, the radio frequency bias is kept off, and the thickness of the second deposition is 20nm. Step (3) Third deposition: control the lens temperature to 100℃, the ion source power to 100w, the evaporation rate to 0.4nm / s, keep the RF bias off, and the thickness of the third deposition to 61nm; After step (4) deposition is completed, the MgF2 electron beam baffle is turned off, the lens temperature is kept at 100℃, the ion source power is kept at 100w and the argon flow rate is kept at 10 sccm, the bombardment treatment is carried out for 15min, the radio frequency bias is kept off, and then the ion source is turned off. S3: Maintain a vacuum of 2.0×10⁻³Pa for 15 minutes, purge with dry nitrogen to atmospheric pressure, and then slowly cool down to 50℃ at a rate of 2℃ / min to obtain a low-reflectivity lens coating; The low-reflectivity lens coating comprises seven layers from the lens substrate surface outwards: the first layer is SiO2 with a thickness of 15 nm; the second layer is Ti3O5 with a thickness of 10 nm; the third layer is SiO2 with a thickness of 30 nm; the fourth layer is Ti3O5 with a thickness of 40 nm; the fifth layer is SiO2 with a thickness of 20 nm; the sixth layer is Ti3O5 with a thickness of 8 nm; and the seventh layer is MgF2 with a thickness of 85 nm. Among them, the low-reflectivity lens coating has an average reflectivity of ≤0.09% in the 400~1000nm wavelength band and ≤0.1% in the 850nm±50nm range.

[0024] Example 2 This embodiment provides a method for preparing a low-reflectivity lens coating, including the following steps: S1: The glass substrate is placed into the coating machine fixture, evacuated to a vacuum degree ≤2.0×10⁻³Pa, heated to 115℃, activated in situ by low-energy plasma, and cleaned by ion beam to obtain the pretreated lens; The in-situ low-energy plasma surface activation conditions are as follows: using a radio frequency power supply, oxygen flow rate of 11 sccm, power of 160w, and time of 150s. Specifically, the ion beam cleaning process involves using a radio frequency ion source with an Ar flow rate of 13 sccm, a power of 350W, and a cleaning time of 4.5min. S2: On the pretreated lens substrate surface, in the order from the lens substrate surface outward, the following layers are deposited sequentially: the first layer of SiO2; the second layer of Ti3O5; the third layer of SiO2; the fourth layer of Ti3O5; the fifth layer of SiO2; the sixth layer of Ti3O5; and the seventh layer of MgF2 to form an antireflection film system. The third and fifth SiO2 layers both adopted the same preparation steps as the first SiO2 layer, and their deposition was only started after the Ti3O5 layer was prepared and the interlayer treatment was completed. The fourth and sixth Ti3O5 layers both adopted the same preparation steps as the second Ti3O5 layer, and the deposition process only began after the SiO2 layer was prepared and the interlayer treatment was completed. The preparation of the first SiO2 layer includes the following steps: The pretreated lens temperature was kept at 115℃. An oxygen and argon mixture with a flow rate ratio of 2:1 was introduced into the ion source, with oxygen at 12 sccm and argon at 6 sccm. The ion source power was 345W. SiO2 was evaporated by electron beam at a deposition rate of 0.25 nm / s. The radio frequency bias was kept on at 70W throughout the process until the deposition of this layer was completed. The preparation of the second Ti3O5 layer includes the following steps: After the SiO2 layer preceding the Ti3O5 layer is deposited and the interlayer treatment is completed, the temperature is lowered to 105℃, and a mixture of oxygen and argon with a flow rate ratio of 3:1 is introduced, with 15 sccm of oxygen and 5 sccm of argon. The ion source power is 400W. Ti3O5 is evaporated using an electron beam at a deposition rate of 0.03 nm / s, with a 100W RF bias maintained throughout. When 1.3 nm of deposition is achieved, the RF bias is reduced to 70W, the evaporation rate is increased to 0.13 nm / s, the ion source power is maintained at 180W, and the working gas is switched to a mixture of oxygen and argon in equal volume ratios at a total flow rate of 20 sccm, and deposition continues. When only 5 nm of the target thickness of the Ti3O5 layer remains, the ion source gas is switched back to oxygen at a flow rate of 15 sccm until the Ti3O5 layer deposition is complete. This includes interlayer treatment after the deposition of any one layer in the antireflection membrane system and before the deposition of the next layer, specifically: The newly completed film is a Ti3O5 layer. The lens temperature is maintained at 105℃, the ion source is turned on, the power is set to 100w, and argon gas with a flow rate of 11 sccm is introduced to bombard the newly completed film for 3.5 minutes. If the newly completed film is a SiO2 layer, maintain the lens temperature at 115℃, turn on the ion source, set the power to 161w, introduce oxygen at a flow rate of 11 sccm, and apply a 70w radio frequency bias voltage for 38s. The preparation of the 7th MgF2 layer includes the following steps: Step (1) First deposition: control the lens temperature to 105℃, set the ion source power to 230w, introduce argon gas with a flow rate of 10 sccm, MgF2 evaporation rate to 0.3 nm / s, turn off the radio frequency bias, and the first deposition thickness is 4.5nm; Step (2) Second deposition: The lens temperature is controlled at 105℃. During the second deposition, the ion source power is set to slowly decrease from 230W to 100W. During this period, the evaporation rate is 0.45 nm / s, the radio frequency bias is kept off, and the thickness of the second deposition is 21nm. Step (3) Third deposition: control the lens temperature to 105℃, the ion source power to 100w, the evaporation rate to 0.45nm / s, keep the RF bias off, and the thickness of the third deposition to 70.5nm; After step (4) deposition is completed, the MgF2 electron beam baffle is turned off, the lens temperature is kept at 105℃, the ion source power is kept at 100w and the argon flow rate is kept at 10 sccm, the bombardment treatment is carried out for 14min, the radio frequency bias is kept off, and then the ion source is turned off. S3: Maintain a vacuum of 2.0×10⁻³Pa for 15 minutes, purge with dry nitrogen to atmospheric pressure, and then slowly cool down to 50℃ at a rate of 2℃ / min to obtain a low-reflectivity lens coating; The low-reflectivity lens coating comprises seven layers from the lens substrate surface outwards: the first layer is SiO2 with a thickness of 18 nm; the second layer is Ti3O5 with a thickness of 13 nm; the third layer is SiO2 with a thickness of 36 nm; the fourth layer is Ti3O5 with a thickness of 47 nm; the fifth layer is SiO2 with a thickness of 25 nm; the sixth layer is Ti3O5 with a thickness of 10 nm; and the seventh layer is MgF2 with a thickness of 96 nm. Among them, the low-reflectivity lens coating has an average reflectivity of ≤0.09% in the 400~1000nm wavelength band and ≤0.1% in the 850nm±50nm range.

[0025] Example 3 This embodiment provides a method for preparing a low-reflectivity lens coating, including the following steps: S1: The glass substrate is placed into the coating machine fixture, evacuated to a vacuum degree ≤2.0×10⁻³Pa, heated to 120℃, activated in situ by low-energy plasma, and cleaned by ion beam to obtain the pretreated lens; The in-situ low-energy plasma surface activation conditions were as follows: using a radio frequency power supply, oxygen flow rate of 13 sccm, power of 175w, and time of 120s. Specifically, the ion beam cleaning process involves using a radio frequency ion source with an Ar flow rate of 15 sccm, a power of 400W, and a cleaning time of 4 minutes. S2: On the pretreated lens substrate surface, in the order from the lens substrate surface outward, the following layers are deposited sequentially: the first layer of SiO2; the second layer of Ti3O5; the third layer of SiO2; the fourth layer of Ti3O5; the fifth layer of SiO2; the sixth layer of Ti3O5; and the seventh layer of MgF2 to form an antireflection film system. The third and fifth SiO2 layers both adopted the same preparation steps as the first SiO2 layer, and their deposition was only started after the Ti3O5 layer was prepared and the interlayer treatment was completed. The fourth and sixth Ti3O5 layers both adopted the same preparation steps as the second Ti3O5 layer, and the deposition process only began after the SiO2 layer was prepared and the interlayer treatment was completed. The preparation of the first SiO2 layer includes the following steps: The pretreated lens temperature was kept at 120℃. An oxygen and argon mixture with a flow rate ratio of 2:1 was introduced into the ion source, with oxygen at 12 sccm and argon at 6 sccm. The ion source power was 350W. SiO2 was evaporated by electron beam at a deposition rate of 0.3 nm / s. The radio frequency bias was kept on at 70W throughout the process until the deposition of this layer was completed. The preparation of the second Ti3O5 layer includes the following steps: After the SiO2 layer preceding the Ti3O5 layer is deposited and the interlayer treatment is completed, the temperature is lowered to 110℃, and a mixture of oxygen and argon with a flow rate ratio of 3:1 is introduced, with 15 sccm of oxygen and 5 sccm of argon. The ion source power is 400W. Ti3O5 is evaporated using an electron beam at a deposition rate of 0.04 nm / s, with a 100W RF bias maintained throughout. When 1.6 nm of deposition is achieved, the RF bias is reduced to 70W, the evaporation rate is increased to 0.17 nm / s, the ion source power is maintained at 180W, and the working gas is switched to a mixture of oxygen and argon in equal volume ratios at a total flow rate of 20 sccm, and deposition continues. When only 5 nm of the target thickness of the Ti3O5 layer remains, the ion source gas is switched back to oxygen at a flow rate of 15 sccm until the Ti3O5 layer deposition is complete. This includes interlayer treatment after the deposition of any one layer in the antireflection membrane system and before the deposition of the next layer, specifically: The newly completed film is a Ti3O5 layer. The lens temperature is maintained at 110℃, the ion source is turned on, the power is set to 100w, and argon gas with a flow rate of 12 sccm is introduced to bombard the newly completed film for 3 minutes. If the newly completed film is a SiO2 layer, maintain the lens temperature at 120℃, turn on the ion source, set the power to 175w, introduce oxygen at a flow rate of 12 sccm, and apply a 70w radio frequency bias voltage for 35s. The preparation of the 7th MgF2 layer includes the following steps: Step (1) First deposition: control the lens temperature to 110℃, set the ion source power to 230w, introduce argon gas with a flow rate of 11 sccm, MgF2 evaporation rate to 0.35 nm / s, turn off the radio frequency bias, and the first deposition thickness is 5nm; Step (2) Second deposition: The lens temperature is controlled at 110℃. During the second deposition, the ion source power is set to slowly decrease from 230w to 100w. During this period, the evaporation rate is 0.5 nm / s, the radio frequency bias is kept off, and the thickness of the second deposition is 22nm. Step (3) Third deposition: control the lens temperature to 110℃, the ion source power to 100w, the evaporation rate to 0.5nm / s, keep the RF bias off, and the thickness of the third deposition to 82nm; After step (4) deposition is completed, the MgF2 electron beam baffle is turned off, the lens temperature is kept at 110℃, the ion source power is kept at 100w and the argon flow rate is kept at 11 sccm, the bombardment treatment is carried out for 13min, the radio frequency bias is kept off, and then the ion source is turned off. S3: Maintain a vacuum of 2.0×10⁻³Pa for 15 minutes, purge with dry nitrogen to atmospheric pressure, and then slowly cool down to 50℃ at a rate of 2℃ / min to obtain a low-reflectivity lens coating; The low-reflectivity lens coating comprises seven layers from the lens substrate surface outwards: the first layer is SiO2 with a thickness of 22 nm; the second layer is Ti3O5 with a thickness of 17 nm; the third layer is SiO2 with a thickness of 42 nm; the fourth layer is Ti3O5 with a thickness of 55 nm; the fifth layer is SiO2 with a thickness of 30 nm; the sixth layer is Ti3O5 with a thickness of 13 nm; and the seventh layer is MgF2 with a thickness of 109 nm. Among them, the low-reflectivity lens coating has an average reflectivity of ≤0.09% in the 400~1000nm wavelength band and ≤0.1% in the 850nm±50nm range.

[0026] Example 4 This embodiment provides a method for preparing a low-reflectivity lens coating, including the following steps: S1: The glass substrate is placed into the coating machine fixture, evacuated to a vacuum degree ≤2.0×10⁻³Pa, heated to 125℃, activated by in-situ low-energy plasma, and cleaned by ion beam to obtain the pretreated lens; The in-situ low-energy plasma surface activation conditions were as follows: using a radio frequency power supply, oxygen flow rate of 14 sccm, power of 182w, and time of 90s. Specifically, the ion beam cleaning process involves using a radio frequency ion source with an Ar flow rate of 18 sccm, a power of 450W, and a cleaning time of 3.5min. S2: On the pretreated lens substrate surface, in the order from the lens substrate surface outward, the following layers are deposited sequentially: the first layer of SiO2; the second layer of Ti3O5; the third layer of SiO2; the fourth layer of Ti3O5; the fifth layer of SiO2; the sixth layer of Ti3O5; and the seventh layer of MgF2 to form an antireflection film system. The third and fifth SiO2 layers both adopted the same preparation steps as the first SiO2 layer, and their deposition was only started after the Ti3O5 layer was prepared and the interlayer treatment was completed. The fourth and sixth Ti3O5 layers both adopted the same preparation steps as the second Ti3O5 layer, and the deposition process only began after the SiO2 layer was prepared and the interlayer treatment was completed. The preparation of the first SiO2 layer includes the following steps: The pretreated lens temperature was kept at 125℃. An oxygen and argon mixture with a flow rate ratio of 2:1 was introduced into the ion source, with oxygen at 12 sccm and argon at 6 sccm. The ion source power was 355W. SiO2 was evaporated by electron beam at a deposition rate of 0.35 nm / s. The radio frequency bias was kept on at 70W throughout the process until the deposition of this layer was completed. The preparation of the second Ti3O5 layer includes the following steps: After the SiO2 layer preceding the Ti3O5 layer is deposited and the interlayer treatment is completed, the temperature is lowered to 115℃, and a mixture of oxygen and argon with a flow rate ratio of 3:1 is introduced, with 15 sccm of oxygen and 5 sccm of argon. The ion source power is 400W. Ti3O5 is evaporated using an electron beam at a deposition rate of 0.045 nm / s. The RF bias is maintained at 100W throughout the process. When 1.9nm has been deposited, the RF bias is reduced to 70W, the evaporation rate is increased to 0.21nm / s, the ion source power is maintained at 180W, and the working gas is switched to a mixture of oxygen and argon in equal volume ratios at a total flow rate of 20 sccm. Deposition continues. When only 5nm of the target thickness of the Ti3O5 layer remains, the ion source gas is switched back to oxygen at a flow rate of 15 sccm until the Ti3O5 layer deposition is complete. This includes interlayer treatment after the deposition of any one layer in the antireflection membrane system and before the deposition of the next layer, specifically: The newly completed film is a Ti3O5 layer. The lens temperature is maintained at 115℃, the ion source is turned on, the power is set to 100w, and argon gas with a flow rate of 14sccm is introduced to bombard the newly completed film for 2.5 minutes. If the newly completed film is a SiO2 layer, maintain the lens temperature at 125℃, turn on the ion source, set the power to 183w, introduce oxygen at a flow rate of 14 sccm, and apply a 70w radio frequency bias voltage for 32s. The preparation of the 7th MgF2 layer includes the following steps: Step (1) First deposition: control the lens temperature to 115℃, set the ion source power to 230w, introduce argon gas with a flow rate of 11 sccm, MgF2 evaporation rate to 0.37 nm / s, turn off the radio frequency bias, and the first deposition thickness is 5.5nm; Step (2) Second deposition: The lens temperature is controlled at 115℃. During the second deposition, the ion source power is set to slowly decrease from 230W to 100W. During this period, the evaporation rate is 0.55 nm / s, the radio frequency bias is kept off, and the thickness of the second deposition is 23nm. Step (3) Third deposition: control the lens temperature to 115℃, the ion source power to 100w, the evaporation rate to 0.55nm / s, keep the RF bias off, and the thickness of the third deposition to 92.5nm; After step (4) deposition is completed, the MgF2 electron beam baffle is turned off, the lens temperature is kept at 115℃, the ion source power is kept at 100w and the argon flow rate is kept at 11 sccm, the bombardment is carried out for 11min, the radio frequency bias is kept off, and then the ion source is turned off. S3: Maintain a vacuum of 2.0×10⁻³Pa for 15 minutes, purge with dry nitrogen to atmospheric pressure, and then slowly cool down to 50℃ at a rate of 2℃ / min to obtain a low-reflectivity lens coating; The low-reflectivity lens coating comprises seven layers from the lens substrate surface outwards: the first layer is SiO2 with a thickness of 26 nm; the second layer is Ti3O5 with a thickness of 21 nm; the third layer is SiO2 with a thickness of 48 nm; the fourth layer is Ti3O5 with a thickness of 62 nm; the fifth layer is SiO2 with a thickness of 35 nm; the sixth layer is Ti3O5 with a thickness of 16 nm; and the seventh layer is MgF2 with a thickness of 121 nm. Among them, the low-reflectivity lens coating has an average reflectivity of ≤0.09% in the 400~1000nm wavelength band and ≤0.1% in the 850nm±50nm range.

[0027] Example 5 This embodiment provides a method for preparing a low-reflectivity lens coating, including the following steps: S1: The glass substrate is placed into the coating machine fixture, evacuated to a vacuum degree ≤2.0×10⁻³Pa, heated to 130℃, activated by in-situ low-energy plasma, and cleaned by ion beam to obtain the pretreated lens; The in-situ low-energy plasma surface activation conditions are as follows: using a radio frequency power supply, oxygen flow rate of 15 sccm, power of 200w, and time of 60s. Specifically, the ion beam cleaning process involves using a radio frequency ion source with an Ar flow rate of 20 sccm, a power of 500w, and a cleaning time of 3min. S2: On the pretreated lens substrate surface, in the order from the lens substrate surface outward, the following layers are deposited sequentially: the first layer of SiO2; the second layer of Ti3O5; the third layer of SiO2; the fourth layer of Ti3O5; the fifth layer of SiO2; the sixth layer of Ti3O5; and the seventh layer of MgF2 to form an antireflection film system. The third and fifth SiO2 layers both adopted the same preparation steps as the first SiO2 layer, and their deposition was only started after the Ti3O5 layer was prepared and the interlayer treatment was completed. The fourth and sixth Ti3O5 layers both adopted the same preparation steps as the second Ti3O5 layer, and the deposition process only began after the SiO2 layer was prepared and the interlayer treatment was completed. The preparation of the first SiO2 layer includes the following steps: The pretreated lens temperature was kept at 130℃. An oxygen and argon mixture with a flow rate ratio of 2:1 was introduced into the ion source, with oxygen at 12 sccm and argon at 6 sccm. The ion source power was 360W. SiO2 was evaporated by electron beam at a deposition rate of 0.4 nm / s. The radio frequency bias was kept on at 70W throughout the process until the deposition of this layer was completed. The preparation of the second Ti3O5 layer includes the following steps: After the SiO2 layer preceding the Ti3O5 layer is deposited and the interlayer treatment is completed, the temperature is lowered to 120℃, and a mixture of oxygen and argon with a flow rate ratio of 3:1 is introduced, with 15 sccm of oxygen and 5 sccm of argon. The ion source power is 400W. Ti3O5 is evaporated using an electron beam at a deposition rate of 0.05 nm / s, with a 100W RF bias maintained throughout. When 2.2nm of Ti3O5 has been deposited, the RF bias is reduced to 70W, the evaporation rate is increased to 0.25 nm / s, the ion source power is maintained at 180W, and the working gas is switched to a mixture of oxygen and argon in equal volume ratios at a total flow rate of 20 sccm, and deposition continues. When only 5nm of Ti3O5 layer thickness remains to be deposited, the ion source gas is switched back to oxygen at a flow rate of 15 sccm until the Ti3O5 layer deposition is complete. This includes interlayer treatment after the deposition of any one layer in the antireflection membrane system and before the deposition of the next layer, specifically: The newly completed film is a Ti3O5 layer. The lens temperature is maintained at 120℃, the ion source is turned on, the power is set to 100w, and argon gas with a flow rate of 15 sccm is introduced to bombard the newly completed film for 2 minutes. If the newly completed film is a SiO2 layer, maintain the lens temperature at 130℃, turn on the ion source, set the power to 200W, introduce oxygen at a flow rate of 15 sccm, and apply a 70W radio frequency bias voltage for 30 seconds. The preparation of the 7th MgF2 layer includes the following steps: Step (1) First deposition: control the lens temperature to 120℃, set the ion source power to 230w, introduce argon gas with a flow rate of 12 sccm, MgF2 evaporation rate to 0.4 nm / s, turn off the radio frequency bias, and the first deposition thickness is 6nm; Step (2) Second deposition: The lens temperature is controlled at 120°C. During the second deposition, the ion source power is set to slowly decrease from 230W to 100W. During this period, the evaporation rate is 0.6 nm / s, the radio frequency bias is kept off, and the thickness of the second deposition is 24nm. Step (3) Third deposition: control the lens temperature to 120℃, the ion source power to 100w, the evaporation rate to 0.6nm / s, keep the RF bias off, and the thickness of the third deposition to 100nm; After step (4) deposition is completed, the MgF2 electron beam baffle is turned off, the lens temperature is kept at 120°C, the ion source power is kept at 100W and the argon flow rate is kept at 12 sccm, the bombardment is carried out for 10 minutes, the radio frequency bias is kept off, and then the ion source is turned off. S3: Maintain a vacuum of 2.0×10⁻³Pa for 15 minutes, purge with dry nitrogen to atmospheric pressure, and then slowly cool down to 50℃ at a rate of 2℃ / min to obtain a low-reflectivity lens coating; The low-reflectivity lens coating comprises seven layers from the lens substrate surface outwards: the first layer is SiO2 with a thickness of 30 nm; the second layer is Ti3O5 with a thickness of 25 nm; the third layer is SiO2 with a thickness of 55 nm; the fourth layer is Ti3O5 with a thickness of 70 nm; the fifth layer is SiO2 with a thickness of 40 nm; the sixth layer is Ti3O5 with a thickness of 18 nm; and the seventh layer is MgF2 with a thickness of 130 nm. Among them, the low-reflectivity lens coating has an average reflectivity of ≤0.09% in the 400~1000nm wavelength band and ≤0.1% in the 850nm±50nm range.

[0028] The ion sources in Examples 1-5 are all radio frequency ion sources.

[0029] Comparative Example 1 This comparative example uses a conventional vacuum sputtering method to prepare a low-reflectivity lens coating. The thickness of the low-reflectivity lens coating in the comparative example is the same as that in Example 1, and the antireflection film system is the same. Specifically, the low-reflectivity lens coating comprises seven layers from the lens substrate surface outwards: the first layer is SiO2 with a thickness of 15 nm; the second layer is Ti3O5 with a thickness of 10 nm; the third layer is SiO2 with a thickness of 30 nm; the fourth layer is Ti3O5 with a thickness of 40 nm; the fifth layer is SiO2 with a thickness of 20 nm; the sixth layer is Ti3O5 with a thickness of 8 nm; and the seventh layer is MgF2 with a thickness of 85 nm.

[0030] Performance testing: (1) The reflectance of the low-reflectance lens coatings of Example 1 and Comparative Example 1 in the wavelength range of 380~1080 nm was tested using a UV-Vis-NIR transmission spectrometer (UV3600plus, Tokyo, Japan) equipped with an integrating sphere accessory ISR-2600Plus. The corresponding relationship between the reflectance and wavelength of the low-reflectance lens coatings of Example 1 and Comparative Example 1 was obtained. The specific test results are as follows: Figure 1 As shown; from Figure 1 It can be seen that the average reflectivity of the low-reflectivity lens coating in Example 1 of this invention is significantly lower than that of the coating prepared in Comparative Example 1 in the 400~1000nm wavelength band. Especially in the target wavelength range of 850nm±50nm, the reflectivity advantage of the coating of this invention is more prominent, which can better meet the performance requirements of low-reflectivity lenses for applications such as near-infrared optical imaging and laser sensing. Figure 2It can be seen that as the incident angle of light increases, the lowest reflection wavelength corresponding to the destructive interference of the thin film exhibits a slight blue shift. In Embodiment 1 of this invention, the total drift of the lowest reflection valley is only 30-40 nm within the incident angle range of 0°~40°, and low reflectivity is maintained continuously in the 800-900 nm infrared supplementary light band. Simultaneously, the film system in Embodiment 1 effectively suppresses the reflection difference between S-polarization and P-polarization, ensuring good light transmission uniformity for the wide-angle security lens even under large incident angle fields of view. This effectively reduces the problem of uneven light transmission caused by polarization differences under large angle fields of view, improves image vignetting, and ensures consistent brightness across the entire field of view under both daytime visible light and nighttime infrared supplementary light conditions. In summary, the low-reflectivity lens coating of this invention not only possesses excellent anti-reflection performance in normally incident scenarios but also maintains stable and outstanding low-reflection characteristics in wide-angle optical applications with large incident angles. This fully demonstrates that the low-reflectivity lens coating provided by this invention can effectively optimize the density and interface bonding of the film layer, ultimately achieving a stable anti-reflection effect over a wide angle range.

[0031] (2) Adhesion test: The test was conducted according to ASTM D3359 standard. A 6×6 grid was drawn on the surface of the low reflectivity lens coating in Examples 1-5 and Comparative Example 1. Debris in the grid area was removed, and standard 3M tape was evenly applied to the grid area and pressed firmly. After standing for 90 seconds, the tape was quickly peeled off. The peeling situation was observed, and the grade was determined according to the standard (test standard: 0B: peeling of more than 65%; 1B: peeling of more than 35% and less than 65%; 2B: peeling of more than 15% and less than 35%; 3B: peeling of more than 5% and less than 15%; 4B: peeling of less than 5%; 5B: no peeling). The specific test results are shown in Table 1. (3) Test of resistance to damp heat: The test was conducted in accordance with GB / T 2423.3 "Constant damp heat test" with an incident angle of 8˚, temperature of 60±5℃, relative humidity of 85±5%RH, and time of 50h. The average reflectance (%) of the low reflectance lenses in Examples 1-5 and Comparative Example 1 before and after the experiment was recorded. The test was repeated three times and the average value was recorded. The damp heat resistance was expressed by the retention rate (%) of the average reflectance. The specific test results are shown in Table 1. (4) Contact angle test: The static water contact angle of the low reflectivity lens coating surface in Examples 1-5 and Comparative Example 1 was measured using a contact angle goniometer. The test solution was deionized water. The contact angle was determined by the goniometer method. Each group was repeated 3 times and the average value was recorded. The specific test results are shown in Table 1.

[0032] As shown in Table 1, the low-reflectivity lens coating provided by this invention exhibits significant improvements in all performance aspects compared to the comparative example. Regarding adhesion, all embodiments achieved an adhesion grade of 5B, far superior to the 3B of the comparative example, indicating a stronger bond between the low-reflectivity lens coating and the glass substrate. In terms of resistance to damp heat, the average reflectivity retention rate after experiments in all embodiments was 98.66%, significantly higher than the 82.1% of the comparative example, demonstrating that the coating maintains stable optical performance under damp heat conditions and exhibits excellent environmental stability. The water contact angle of the low-reflectivity lens coating prepared by this invention is consistently above 116°, significantly higher than the 105.7° of the comparative example, indicating that the low-reflectivity lens coating of this invention possesses better hydrophobic properties, is less prone to water and oil adhesion, and is easier for daily cleaning and maintenance. In summary, the low-reflectivity lens coating prepared by this invention demonstrates comprehensive improvements in adhesion, weather resistance, optical performance, and anti-fouling properties, meeting the requirements for application in camera lenses and vehicle security lenses.

[0033] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

[0034] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0035] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low-reflectivity lens coating, characterized in that, The lens substrate consists of seven layers from the surface outwards: the first layer is SiO2 with a thickness of 15-30 nm; the second layer is Ti3O5 with a thickness of 10-25 nm; the third layer is SiO2 with a thickness of 30-55 nm; the fourth layer is Ti3O5 with a thickness of 40-70 nm; the fifth layer is SiO2 with a thickness of 20-40 nm; the sixth layer is Ti3O5 with a thickness of 8-18 nm; and the seventh layer is MgF2 with a thickness of 85-130 nm. Among them, the low-reflectivity lens coating has an average reflectivity of ≤0.09% in the 400~1000nm wavelength band and ≤0.1% in the 850nm±50nm range.

2. A method for preparing a low-reflectivity lens coating, used to prepare the low-reflectivity lens coating as described in claim 1, characterized in that, The preparation method includes: S1: The lens substrate is loaded into the coating machine fixture, vacuumed, heated, in-situ low-energy plasma surface activation, and ion beam cleaning to obtain the pretreated lens. S2: Layers 1 to 7 are deposited sequentially on the pretreated lens substrate surface in an order from the lens substrate surface outward to form an antireflective coating system; S3: Deposit all film layers, post-process, to obtain a low-reflectivity lens coating; The antireflective coating system consists of the following layers from the surface of the lens substrate outwards: a first layer of SiO2; a second layer of Ti3O5; a third layer of SiO2; a fourth layer of Ti3O5; a fifth layer of SiO2; a sixth layer of Ti3O5; and a seventh layer of MgF2. In S1, the lens substrate is glass; In S1, the vacuum level after evacuation is ≤2.0×10⁻⁶. -3 Pa; The third and fifth SiO2 layers both follow the same preparation steps as the first SiO2 layer, and deposition only begins after the Ti3O5 layer is prepared and the interlayer treatment is completed. The fourth and sixth Ti3O5 layers both follow the same preparation steps as the second Ti3O5 layer, and deposition only begins after the SiO2 layer is prepared and the interlayer treatment is completed.

3. The method for preparing a low-reflectivity lens coating according to claim 2, characterized in that, The preparation of the first SiO2 layer includes the following steps: The pretreated lens temperature was maintained at 110~130℃. An oxygen-argon mixture with a flow rate ratio of 2:1 was introduced into the ion source, with 12 sccm of oxygen and 6 sccm of argon. The ion source power was 340~360W. SiO2 was evaporated by electron beam at a deposition rate of 0.2~0.4 nm / s. The radio frequency bias voltage was 70W and kept on throughout the process until the deposition of the layer reached the required thickness.

4. The method for preparing a low-reflectivity lens coating according to claim 2, characterized in that, The preparation of the second Ti3O5 layer includes the following steps: After the SiO2 layer preceding the Ti3O5 layer is deposited and the interlayer treatment is completed, the temperature is lowered to 100-120℃, and a mixture of oxygen and argon with a flow rate ratio of 3:1 (15 sccm oxygen, 5 sccm argon) is introduced, with an ion source power of 400W. Ti3O5 is evaporated using an electron beam at a deposition rate of 0.03-0.05 nm / s, with a 100W RF bias maintained throughout. When 1-2.2 nm of deposition is achieved, the RF bias is reduced to 70W, the evaporation rate is increased to 0.1-0.25 nm / s, the ion source power is maintained at 180W, and the working gas is switched to an equal volume ratio mixture of oxygen and argon at a total flow rate of 20 sccm, continuing deposition. When only 5 nm of the target Ti3O5 layer thickness remains, the ion source gas is switched back to oxygen at a flow rate of 15 sccm until the Ti3O5 layer reaches the desired thickness.

5. The method for preparing a low-reflectivity lens coating according to claim 2, characterized in that, After the deposition of any one layer in the antireflection film system is completed, before the deposition of the next layer, an interlayer treatment is also included, specifically: If the newly completed film is a Ti3O5 layer, maintain the lens temperature at 100~120℃, turn on the ion source, set the power to 100w, and introduce argon gas at a flow rate of 10~15 sccm to bombard the newly completed film for 2 minutes. If the newly completed film is a SiO2 layer, maintain the lens temperature at 110~130℃, turn on the ion source, set the power to 150~200w, introduce oxygen at a flow rate of 10~15 sccm, and simultaneously apply a 70w radio frequency bias voltage for 30~40s.

6. The method for preparing a low-reflectivity lens coating according to claim 2, characterized in that, The preparation of the 7th MgF2 layer includes the following steps: Step (1) First deposition: The ion source power was set to 230W, the argon gas flow rate was 10~12 sccm, the MgF2 evaporation rate was 0.3~0.4 nm / s, the radio frequency bias was turned off, and the first deposition thickness was 4~6nm. Step (2) Second deposition: During the second deposition, the ion source power was slowly reduced from 230W to 100W, the evaporation rate was 0.4–0.6 nm / s, and the thickness of the second deposition was 20–24 nm. Step (3) Third deposition: The ion source power was set to 100W, the evaporation rate was 0.4–0.6 nm / s, and the thickness of the third deposition was 61–100 nm. After step (4) deposition is completed, turn off the MgF2 electron beam baffle, maintain the ion source power at 100W and the argon flow rate at 10~12sccm, bombard for 10~15min, and then turn off the ion source; In steps (1), (2), (3), and (4), the lens temperature is maintained at 100~120℃, and the radio frequency bias voltage is kept off.

7. The method for preparing a low-reflectivity lens coating according to claim 2, characterized in that, The post-processing steps are as follows: After all the film layers are deposited, maintain vacuum for 15 minutes, purge with dry nitrogen to atmospheric pressure, and then slowly cool to 50°C at a rate of 2°C / min before removing.

8. A low-reflectivity lens, characterized in that, Including the low-reflectivity lens coating as described in claim 1.

9. A low-reflectivity glass, characterized in that, Including the low-reflectivity lens coating as described in claim 1.

10. A security camera for vehicles, characterized in that, Including the low-reflectivity lens coating as described in claim 1.

Citation Information

Patent Citations

  • A 1.56 refractive index low reflectivity film resin lens and its coating method

    CN103698901B

  • Low-reflectivity lens and preparation method thereof

    CN118688882A